The People's Health - Hastings, Somerville, 1878-1967 (London : The Labour Party)
1932-07 1932 1930s 24 pages housing conditions. Of equal importance are careful and repeated pre-natal examinations by doctors with special experience. By this means at least half the conditions which are the cause of maternal mortality can be recognised and dealt with. An attempt should be made to persuade every mother to have her baby in a maternity hospital. Experience shows that these hospitals are most successful when they contain not more than 100 beds and have ample isolation accommodation. A capable medical officer must be available in the hospitals at all times, both day and night. An ambulance service should bring the patient to hospital and carry everything necessary in case of precipitate delivery. For those apparently normal pregnant women who insist on having their babies at home, the services of midwife will be provided, and she will send for an obstetrician when required. Pathology. It is important that pathology should not be divorced from clinical medicine. Pathologists, physicians and surgeons must work together in close association. Pathological laboratories will, therefore, be required in all Health Centres and Hospitals, and in addition in most counties a special laboratory will be needed for the production of ant-toxins [anti-toxins], sera, &c. The detailed organisation of the required laboratory services is best left to a representative committee of the pathologists of the county. Every laboratory will be staffed by at least one technician and one medically qualified pathologist who may be part-time, i.e., undertake duty at more than one laboratory. The laboratories will be grouped in areas and a larger "Group" laboratory will supply Media, Stains, &c., to its satelites [satellites] and carry out special and difficult investigations. Most of the research work will be done in these "Group" laboratories. Research. Money wisely spent on research is money well spent, but this alone will not provide the genius capable of original research, which is even more important than money. Means must be found for seeking out the right type of person, and the first step should be a radical alteration in the whole system of medical education and in the method of selecting those who are to be the doctors and scientists of the future. It must be remembered that there is no monopoly of genius in any one class of the community, and that the science of medicine owes much of its present broad basis to Louis Pasteur, the son of a French peasant. If sufficient men and women endowed by nature with power to advance science are to be found, the doors of our universities and medical schools must be thrown 13 292C/155/1/1